Some Hematological and biochemical changes in blood serum of Beluga (Huso huso) after chronic exposure to diazinon - Khoshbaver Rostami, H.A.; Soltani, M.; Hassan, M.D. (2006)
Hematological and biochemical changes were studied in beluga (Huso huso) weighing 450±50g in the presence of b,1-3, D-glucan as a single intraperitoneal injection (0.3mg/kg body weight) once, and thereafter a chronic exposure to organophosphate, diazinon at concentration of 1.5 mg/L as a continuous bath for 63 days at 22±1ºC. Results of erythrocyte profile in fish treated with glucan, but without diazinon, generally showed significant higher values of RBC (P<0.05) compare to fish treated with glucan plus diazinon bath, while there was no significant difference (P>0.05) in the values of HCT, Hb, MCH and MCHC between the two groups. Also, fish treated with glucan, but without diazinon bath, showed significant higher values of RBC than that untreated fish up to 3 weeks post-treatment (P<0.05), while no significant differences was found in other erythrocytic indices between these two groups (P>0.05). Furthermore, fish treated with diazinon showed higher levels of alkaline phosphatase (ALP), alanine aminotransferase (ALT), lactate dehydrogenase (LDH) than other three groups for 14-28 days post-treatment and then they decreased to the lower level for the rest of experiment. Also, fish treated with glucan-diazinon showed insignificant higher levels of these enzymes up to 21 days post-exposure compare to fish treated with glucan but without diazinon bath (P>0.05). However, such levels reduced to a lower level in this group for the rest of experiment (P>0.05). Also, fish treated with glucan-diazinon showed generally lower and higher levels of total protein and glucose concentrations in blood plasma, respectively compared to fish treated with glucan but without diazinon bath (P<0.05). Published